O desenvolvimento de competências dos oficiais da linha bélica do exército brasileiro para o desempenho de funções administrativas - RAMOS, Leandro Silva de Moraes (2013)
The theme of developing competencies to the performance of administrative functions by commissioned line officers of the Brazilian Army emerged from the observation of this author on the difficulties presented by these professionals in the execution of administrative activities. Departing from this observation, this research aims at analyzing the development of competencies of Brazilian line officers in institutional courses for career progression designed to meet the demands of administrative functions. To this end, it is presented the organizational structure of the Brazilian Army, it is reviewed the basis on the State Reform and the new demands imposed on the training of its managers, it is discussed the concepts of competency and its constituency, and it is analyzed the courses for career progression of the line officer. A field research was carried out with all the line officers belonging to the 6th Military Region, which encompasses the States of Bahia and Sergipe, amounting to 157 answered questionnaires. They were all interviewed on the training received to the performance of administrative activities. The assumed hypothesis was that there is a need for reformulation in the courses for career progression of line officers related to the preparation for performing administrative functions. Results show that there is development of competencies to perform administrative functions in the courses for career progression of line officers and that it is desirable to have an increase of instruction time in the subjects related to this theme.